13C nuclear magnetic resonance studies of anaerobic glycolysis in Trypanosoma brucei spp. Issue 2 (February 1983) - Mackenzie, N. E.; Hall, James Edwin; Flynn, I. W.; Scott, A. I.
Abstract : Anaerobic glycolysis in Trypanosoma brucei spp. has been studied by 13 C NMR at 50 and 75.5 MHz. The uptake of [U- 13 C]glucose by cell suspensions of T. b. brucei was monitored by time-course spectroscopy, and while no anomeric specificity was found, the end -products of glycolysis were confirmed as glycerol and pyruvate together with alanine and dihydroxypropionat e. The intermediacy of L-glycerol-3-phosphate was also ascertained. The incorporation of C-I of [1- 13 C]glucose and of C-6 of [6- 13 C]glucose into glycerol and pyruvate in T. b. gambiense was quantified by measurement of the longitudinal relaxation times of the species involved. An incorporation to the extent of 66% of each substrate into equimolar amounts of glycerol and pyruvate indicate that Keq for the triosephosphate-isomerase-mediated reaction approaches unity.